Engineering Standards: An Introduction for Electrical and Computer Engineering Students - Attia, John O.; Vaman, Dhadesugoor; Sadiku, Matthew N. O. (European Scientific Journal, ESJ, 2017)
Engineering standards are summaries of industrial best practices. The specifications are written in terms of functional, mechanical and electrical aspects that allow proper usage of available components to build a system. Standards may also be regarded as codified guidelines that define how tests should be performed, and how products are to be designed. Standards are created by bringing together experience and expertise of stakeholders on specific issues. Standards protect public health and safety, improve product quality, help to advance the growth of new technologies, and foster international trade. It is important that students get familiar with standards while in school.